MATLAB/simulink modeling of stator current control of PMSG for grid-connected systems - Bunjongjit,K. (2015)
© 2014 IEEE. This paper presents a modeling of stator current control of PMSG for grid-connected systems. The modeling of the power circuit and control-side are performed and represented by using MATLAB/Simulink software to predict and investigate the system operation and the system's dynamic response. Zero-d axis stator current control is implemented to optimize the PMSG for the generator-side converter. The grid-side control scheme decouples active and reactive-power thought voltage-oriented control for the grid-side converter independently. The simulation results are demonstrated to provide the performance and stability of the grid-connected PMSG in the dynamic and steady-state conditions.